Real-time heart rate variability according to ambulatory glucose profile in patients with diabetes mellitus - Im, Sung Il; Kim, Soo Jin; Bae, Su Hyun; Kim, Bong Joon; Heo, Jung Ho; Kwon, Su kyoung; Cho, Sung Pil; Shim, Hun; Park, Jung Hwan; Kim, Hyun Su; Oak, Chul Ho (Frontiers in Cardiovascular Medicine, 2023)
Background: Autonomic neuropathy commonly occurs as a long-term complication of diabetes mellitus (DM) and can be diagnosed based on heart rate variability (HRV), calculated from electrocardiogram (ECG) recordings. There are limited data on HRV using real-time ECG and ambulatory glucose monitoring in patients with DM. The aim of this study was to investigate real-time HRV according to ambulatory glucose levels in patients with DM.Methods: A total of 43 patients (66.3±7.5 years) with DM underwent continuous real-time ECG monitoring (225.7±107.3 hours) for HRV and ambulatory glucose monitoring using a remote monitoring system. We compared the HRV according to the ambulatory glucose profile.Results: There were no significant differences in the baseline characteristics of the patients according to the TIR. During monitoring, we checked ECG and ambulatory glucose levels (a total of 15,090 times) simultaneously for all patients. Both time-and frequency-domain HRVs were lower when the patients had poorly controlled glucose levels (TIR<70%) compared with well controlled glucose levels (TIR>70%). In addition, heart and respiratory rates increased with real-time glucose levels (P<0.001).Poorly controlled glucose levels were independently associated with lower HRV in patients with DM. This was further substantiated by the independent continuous association between real-time measurements of hyperglycemia and lower HRV. These data strongly suggest that cardiac autonomic dysfunction is caused by elevated blood sugar levels.